BH4 domain of Bcl-2 as a novel target for cancer therapy. Issue 6 (June 2016) - Liu, Zhiqing; Wild, Christopher; Ding, Ye; Ye, Na; Chen, Haiying; Wold, Eric A.; Zhou, Jia
Highlights: No Bcl-2 inhibitors targeting the BH3 domain approved for clinical use. BH4 domain of Bcl-2 is identified as a promising novel target for cancer therapy. Bcl-2 BH4 domain interacts with Bcl-2 family members as well as non-Bcl-2 proteins. Interactions of BH4 domain with various proteins promote resistance to apoptosis. Targeting the BH4 domain of Bcl-2 offers great potential to overcome drug resistance. Abstract : Overexpression of B cell lymphoma 2 (Bcl-2) proteins is associated with therapy resistance in various human cancers. Traditional approaches target the Bcl-2 homology (BH)3 domain of Bcl-2; however, the BH4 domain represents a superior therapeutic target in light of its unique structure and crucial involvement in many cellular functions. In this critical review, we focus on the structural and functional basis of targeting the BH4 domain of Bcl-2, and highlight the recent advances in drug discovery efforts toward small-molecule BH4 domain inhibitors (e.g. BDA-366). The proof-of-concept studies support the hypothesis that targeting the BH4 domain of Bcl-2 holds promise to offer a novel anticancer therapy through the induction of apoptosis and an increased potential to overcome therapeutic resistance.